Umami Flavor Formulation of Agarwood Leaf Extract Powder - RAMIZU, NAJWA UMAIRAH; A.TALIP, BALKIS (Enhanced Knowledge in Sciences and Technology, 2024)
Fragrant, black, and resinous, agarwood (Aquilaria spp.) is utilised in many products, such as oils, incense, and perfumes. It has been utilised for medicinal purposes for thousands of years and is also employed in traditional medicine. One of the priciest non-timber wood products available worldwide is agarwood. Thus, another choice is to use the agarwood leaves because it is easier to find to be used in a variety of products. Although this leaf extract has been processed into a powder, the powder has an unpleasant, bitter taste. Therefore, the goal of this project is to transform the bitter taste of agarwood leaves into an umami taste and make them taste more appetising. Along with sweet, salty, sour, and bitter, the five basic flavours are umami, or savoriness. Bromelain enzyme has been used in the enzyme hydrolysis process to extract the umami flavour from this powder. Following that, three sample formulations were made which is formulation one with 83.71% agarwood powder, 8.37% salt, 3.96% sugar and 3.96% sodium benzoate. The second formulation with the percentage of agarwood powder 93.91%, 3.13% salt, 1.48% sugar and 1.48% sodium benzoate and the last formulation is formulation 3 with 96.25% agarwood powder, 1.93% salt, 0.91% sugar and 0.91% sodium benzoate. These three samples will then go through two types of sensory evaluation, namely a 7-point hedonic test and also a descriptive test with the aim of knowing the consumer’s acceptance of this powder to be used in other products such as seasoning and also as a salt substitute. The results of this test will then be evaluated using the ANOVA test. As a result, the best sample is the sample with the second formulation which uses 93.91% agarwood powder because it tastes not too salty and not too bitter with a mean score of 6.26 ± 0.876.